Pengaruh Literasi Keuangan, Pengetahuan Investasi, Motivasi dan Manfaat Investasi Terhadap Minat Mahasiswa dalam Berinvestasi di Pasar Modal (Studi Kasus Mahasiswa di Kota Malang) - Sopia Sopia; Maslichah Maslichah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This research intends to ascertain how investing knowledge, motivation, and imbalanced investment returns impact students' desire in taking part in the capital market. 246 current undergraduate accounting students from the 2019 classes of the Islamic University of Malang, State University of Malang, and University of Muhammadiyah Malang participated in this quantitative survey. A Likert-based questionnaire was utilized in this research to gather data. These were the responses: One strongly disagrees, two disagree, three disagree, four agree, and five disagree. According to the findings of the study conducted on the Class of 2019 Dynamic S1 Bookkeeping students, undergrads' ability to invest in the capital market is significantly influenced by their financial education, venture knowledge, motivation, and advantages from speculating.Keywords: Financial literacy, investment knowledge, motivation, benefits of investment, student interest in investing in the capital market.